2020
DOI: 10.1371/journal.pone.0234475
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Neisseria meningitidis isolates recovered from patients with invasive meningococcal disease in Colombia from 2013 to 2016

Abstract: Background Neisseria meningitidis is a significant cause of morbidity and mortality worldwide. Meningococcal isolates have a highly dynamic population structure and can be phenotypically and genetically differentiated into serogroups and clonal complexes. The aim of this study was to describe the phenotypic and genotypic characteristics of invasive isolates recovered in Colombia from 2013 to 2016. Methodology A total of 193 invasive isolates were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Our data show that there is no prevalent circulation of a single MenB cc in Brazil, which has currently been observed for serogroup B IMD epidemiology in some European countries and not in North America [ 15 , 17 , 34 ]. cc213, cc35, and cc461 have previously been reported in Argentina, Australia, Colombia, Paraguay, Tunisia, Turkey, and Europe [ 23 , 22 , 35 41 ]. Additionally, clonal diversity exhibiting a decline in cc41/44 and cc32 and an increase in cc269 and cc461 was observed in the Republic of Ireland over 19 years [ 39 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our data show that there is no prevalent circulation of a single MenB cc in Brazil, which has currently been observed for serogroup B IMD epidemiology in some European countries and not in North America [ 15 , 17 , 34 ]. cc213, cc35, and cc461 have previously been reported in Argentina, Australia, Colombia, Paraguay, Tunisia, Turkey, and Europe [ 23 , 22 , 35 41 ]. Additionally, clonal diversity exhibiting a decline in cc41/44 and cc32 and an increase in cc269 and cc461 was observed in the Republic of Ireland over 19 years [ 39 ].…”
Section: Discussionmentioning
confidence: 98%
“…Nonetheless, data on the distribution and diversity of these vaccine antigens in Latin America are scarce [ 13 , 22 , 23 ]. Therefore, we aimed to evaluate the genetic lineages, the diversity of vaccine antigens, and the alleles types of antimicrobial resistance-associated genes in serogroup B IMD strains isolated in Brazil from 2016 to 2018 using whole-genome sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…31 Lineage 11.1 was composed of MenB, MenW and mainly MenW strains from South America (Brazil, Argentina and Chile), the original UK and Chinese strains at one extreme, and African strains with Anglo/French Hajj strains, while lineage 11.2 was composed only by MenB and MenC isolates from Canada, South Africa and European countries. 31 In the last decades, publications on molecular information in Latin America have increased, evidencing that in Colombia, cc ST-9493 was observed in MenB between 2013 and 2016 32 and in Chile, since 2011, there was an increase in cases of IMD due to cc ST11, with predominance over the other cc during 2012 and 2013. 17,33,34 Most MenW cc ST-11 strains in this study had an antigen profile: W:P1.5,2:ST-11 (cc11) and fHbp allele 22, which differs from MenW strains identified in Brazilian in recent years (W:P1.5,2:ST-11) with a novel fHbp peptide 1241, 35 or fHbp peptide 24 in MenB.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, publications on molecular information in Latin America have increased, evidencing that in Colombia, cc ST-9493 was observed in MenB between 2013 and 2016 32 and in Chile, since 2011, there was an increase in cases of IMD due to cc ST11, with predominance over the other cc during 2012 and 2013. 17,33,34 Most MenW cc ST-11 strains in this study had an antigen profile: W:P1.5,2:ST-11 (cc11) and fHbp allele 22, which differs from MenW strains identified in Brazilian in recent years (W:P1.5,2:ST-11) with a novel fHbp peptide 1241, 35 or fHbp peptide 24 in MenB.…”
Section: Discussionmentioning
confidence: 99%
“…Some Lithuanian MenB isolates (9.0%) were not assigned to any clonal complex, whereas isolates of ccUA accounted for 22% in Norway, 19.4% in Germany, 9.3% in Italy ( Vogel et al., 2013 ), 20.2% in Poland ( Waśko et al., 2020 ), and 6.1% in Greece ( Tzanakaki et al., 2021 ). The predicted coverage data of isolates collected from 2017 to 2019 showed that the antigen peptide variants present in ccUA strains often fall into the grey zone characterized by ‘insufficient data’ or ‘unpredictable’ categories according to the gMATS and/or MenDeVAR Index methods ( Mulhall et al., 2018 ; Moreno et al., 2020 ). The Lithuanian isolates of ccUA were unevenly distributed across age groups, with the highest proportion found among children < 1-year-old ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%